Valuing Health Conditions - Insights from Happiness Surveys across Countries and Cultures - Carol Graham; Lucas Higuera; Eduardo Lora (Inter-American Development Bank (IDB), 2009)
This paper assesses the effects of different health conditions on happiness. Based on a large data set for Latin America, the effects of different conditions are examined across age, gender, and income cohorts. Anxiety and pain have stronger effects than physical problems, likely because people can adapt better to one-time shocks than to constant uncertainty. The negative effects of health conditions are very large when compared to the effects of income on happiness. While higher peer income typically elicits envy, better peer health provides positive signals for life and health satisfaction. Nonetheless, health norms vary widely across countries. The results suggest that the life satisfaction approach applied to surveys of health may contribute to better health expenditure and policy decisions.
Keywords: C83; I18; I30; I38; 330; Happiness; Health economics; Public policy; Surveys